2010
DOI: 10.2337/db09-1200
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness and Insulin Sensitivity in Overweight or Obese Subjects May Be Linked Through Intrahepatic Lipid Content

Abstract: OBJECTIVELow cardiorespiratory fitness (CRF) predisposes one to cardiovascular disease and type 2 diabetes in part independently of body weight. Given the close relationship between intrahepatic lipid content (IHL) and insulin sensitivity, we hypothesized that the direct relationship between fitness and insulin sensitivity may be explained by IHL.RESEARCH DESIGN AND METHODSWe included 138 overweight to obese, otherwise healthy subjects (aged 43.6 ± 8.9 years, BMI 33.8 ± 4 kg/m2). Body composition was estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
31
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 52 publications
9
31
2
Order By: Relevance
“…In overweight non-obese individuals the association of V : O 2max with insulin sensitivity has been explained mainly by intrahepatic lipid content [10]. The present study found a similar association in people with recently diagnosed type 2 diabetes but detected no link with hepatic steatosis.…”
Section: Discussionsupporting
confidence: 65%
“…In overweight non-obese individuals the association of V : O 2max with insulin sensitivity has been explained mainly by intrahepatic lipid content [10]. The present study found a similar association in people with recently diagnosed type 2 diabetes but detected no link with hepatic steatosis.…”
Section: Discussionsupporting
confidence: 65%
“…The etiology of insulin resistance is multifactorial and involves both genetic and environmental factors. 2 Several lines of evidence have been provided in support of the hypothesis that intramyocellular lipids (IMCLs) and intrahepatic lipids (IHLs), as assessed non-invasively by localized 1 H-magnetic resonance spectroscopy, are associated with reduced-insulin action in both obese and non-obese subjects. 2,3 In addition, high IMCL levels are associated with the impairment of early insulin signal transduction in specimens obtained from muscle biopsies, because IMCLs and related intracellular substances, such as diacylglycerol or protein kinase C, are important regulators of insulin resistance in skeletal muscle.…”
mentioning
confidence: 99%
“…2 Several lines of evidence have been provided in support of the hypothesis that intramyocellular lipids (IMCLs) and intrahepatic lipids (IHLs), as assessed non-invasively by localized 1 H-magnetic resonance spectroscopy, are associated with reduced-insulin action in both obese and non-obese subjects. 2,3 In addition, high IMCL levels are associated with the impairment of early insulin signal transduction in specimens obtained from muscle biopsies, because IMCLs and related intracellular substances, such as diacylglycerol or protein kinase C, are important regulators of insulin resistance in skeletal muscle. 4 Insulin-resistant individuals have a reduced rate of fat oxidation, compared with normal, insulin-sensitive individuals, and thus, the decreased mitochondrial fat oxidative capacity could lead to an increase in the intracellular fat content.…”
mentioning
confidence: 99%
See 2 more Smart Citations